Application of theory of planned behavior to evaluate factors that affecting marriage intention of Chinese unmarried women - Chen, Ye; Ma’rof, Aini Azeqa; Abdullah, Haslinda; Hamsan, Hanina Halimatusaadiah; Zaremohzzabieh, Zeinab (Springer, 2025)
This study seeks to uncover the underlying belief structures that shape the cognitive processes behind the intention of unmarried women toward marriage. To achieve this, the extended theory of planned behavior was utilized as the theoretical framework. Quantitative data were collected from 480 unmarried women in China. Structural Equation Modeling was used to analyze the data. This study followed a two-phase survey procedure. In the first phase, the target population’s beliefs were elicited, and in the second phase, the relationships between those beliefs and other theories of planned behavior constructs were analyzed. The findings indicate that the theory of planned behavior model effectively elucidates the formation of marital intentions among these women. Negative and positive behavior beliefs, normative beliefs, and control beliefs serve as foundational elements for shaping marital attitudes, subjective norms, and perceived behavioral control. Notably, marital attitudes, subjective norms, and perceived behavioral control directly influence marriage intentions. This research offers insights into the factors potentially influencing the marriage perspectives of Chinese unmarried women. It emphasizes the need to refine laws and regulations to better safeguard the rights and interests of Chinese women, especially in areas like marriage, childbearing, employment, and career progression. Furthermore, the study advocates for the provision of services like marriage counseling, emotional education, and family counseling through public institutions to bolster the marriage intentions of these women.